2004
DOI: 10.1093/intimm/dxh157
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-1 is expressed on dendritic cells, both in vitro and in vivo

Abstract: Dendritic cells (DCs) are the best professional antigen-presenting cells to stimulate cytotoxic as well as T helper cells and are therefore appropriate candidates for establishing immunotherapy. The concept of our vaccination program is to introduce the tumor-associated antigen mucin-1 (MUC1) into DCs. Analysis of immature and mature DCs--before transducing the antigen MUC1--already demonstrated expression of MUC1 on in vitro monocyte-derived DCs upon maturation. Different culture methods as well as maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…MUC1 protein expression in the thymus has been previously reported, yet the identity of the antigen-expressing cell type(s) remained unclear (21). Moreover, global gene expression analysis by gene arrays had shown that members of the mucin gene family were overexpressed in mTECs (6).…”
Section: Resultsmentioning
confidence: 99%
“…MUC1 protein expression in the thymus has been previously reported, yet the identity of the antigen-expressing cell type(s) remained unclear (21). Moreover, global gene expression analysis by gene arrays had shown that members of the mucin gene family were overexpressed in mTECs (6).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies on mucins in patients with RA, MUC-3 and MUC-5AC were found to be expressed in synovial tissues [25] and MUC-1 was expressed in mononuclear cells in synovial fluid. However, the bioactivity of these mucins was not demonstrated in detail [26,27]. We examined whether mucin-inducing cytokine produc- tion on PBMCs occurs in synovial fluid from patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“…DC were prepared from peripheral blood-derived monocytes as described previously [42] and as control, highly pure monocyte fractions were obtained by elutriation from leukapheresis products of healthy volunteers, approved by the local medical, ethical committee of Maastricht University Medical Center 1 . Differentiation of monocytes was induced by 6 days of culture in AIM-V s medium (Gibco Life Technologies) containing 2000 U/mL IL-4 (Strathmann Biotech) and 400 U/mL GM-CSF (Berlex) or 50 ng/mL IL-13 (Biosource) and 500 U/mL GM-CSF.…”
Section: Generation Of DCmentioning
confidence: 99%